2017
DOI: 10.25046/aj020111
|View full text |Cite
|
Sign up to set email alerts
|

Configuration/Infrastructure-aware testing of MapReduce programs

Abstract: The implemented programs in the MapReduce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Finally, the 47 papers were analyzed thoroughly to determine whether it is possible to extract the data required to answer our stated RQs. During this analysis, we found that some papers were extended versions of previously published conference/workshop papers [26][27][28][29]. Moreover, we were unable to extract data from two papers [30,31].…”
Section: Conducting the Reviewmentioning
confidence: 95%
“…Finally, the 47 papers were analyzed thoroughly to determine whether it is possible to extract the data required to answer our stated RQs. During this analysis, we found that some papers were extended versions of previously published conference/workshop papers [26][27][28][29]. Moreover, we were unable to extract data from two papers [30,31].…”
Section: Conducting the Reviewmentioning
confidence: 95%
“…Other authors [23], [24] identified and classified other design faults that depend upon the infrastructure configurations. In our previous work, we proposed a test approach to detect such faults in the test environment by using a simulation of the infrastructure configurations [26]. In this paper we enhance on that work with a more practical technique that improves efficiency while still detecting the majority of faults by exploiting combinatorial strategies.…”
Section: Related Workmentioning
confidence: 99%
“…In a prior work [26], we proposed an automatic technique that, given test input data, generates a thorough number of configurations (MRTest-Thorough). Then the faults are revealed when a failure occurs in one of these configurations.…”
Section: A Generation Of Infrastructure Configurations For Testingmentioning
confidence: 99%
See 2 more Smart Citations